Evaluating the feasibility of estimating particulate mass emissions of older-model diesel vehicle using smoke opacity measurements - Hsi-Hsien Yang; Amit Kumar; Narayan Babu Dhital; Lin-Chi Wang; Cheng-Hsu Wu; Hesam Kamyab; Mohammad Yusuf (Scientific Reports)
Abstract Real-world emissions of particulate matter (PM) and smoke opacity were studied for an older-model diesel pickup truck during four types of driving tests, namely fixed-point test, snap-acceleration test, road test, and hill road test (uphill/downhill). A portable emissions measurement system (PEMS) and an opacimeter were used to measure real-time concentrations of PM and smoke opacity, respectively, and simultaneously. Correlation analysis showed a significant positive association between PM and opacity, suggesting the feasibility of using an opacimeter to estimate PM mass emissions from diesel vehicles. Additionally, regression analyses were performed to evaluate the relationship between opacity and PM mass concentration. The results of this study indicate that PM emission concentrations from older-model diesel vehicles can be estimated with a reasonable accuracy by using a smoke opacimeter, which is a relatively simple and cost-effective method of emission testing, as an alternative to sophisticated PM measurement instruments.